MENJELAJAH PERSEPSI SISWA TERHADAP PENGGUNAAN APLIKASI KAMUS ONLINE UNTUK MENINGKATKAN PENGUASAAN VOCABULARY: STUDI KASUS PADA SMK DI KABUPATEN SIMALUNGUN - Ayumi Pratiwy Tanjung; Sholihatul Hamidah Daulay (LPPM STKIP Kusuma Negara, 2023)
Online applications are currently growing rapidly in the world of education, one of which is an online dictionary application. The online dictionary application allows students to learn English easily. Therefore, it is necessary to conduct research to determine students' perceptions of the use of online dictionary applications to improve students' vocabulary mastery. This study was formulated to find out students' perceptions of using online dictionaries to improve their vocabulary. The method used is a descriptive qualitative method. The subjects of this study were students of class XI TKJ which consisted of 22 students. The instrument of this research is a questionnaire. The results of this study found that 76% of students believe that learning vocabulary through an online dictionary application can help them improve their vocabulary mastery. The results of this study Â also found that (17) 77% of students most often use online dictionaries rather than printed dictionaries. This is because the online dictionary is an application that is flexible and easy to carry anywhere.